Real-World Evidence of Factors Affecting Cannabidiol Exposure in Children with Drug-Resistant Developmental and Epileptic Encephalopathies - Lucas Brstilo; Gabriela Reyes Valenzuela; Roberto Caraballo; Carlos Pérez Montilla; Facundo García Bournissen; Paulo Cáceres Guido; Paula Schaiquevich (MDPI AG, 2023)
The identification of factors that affect cannabidiol (CBD) systemic exposure may aid in optimizing treatment efficacy and safety in clinical practice. In this study, we aimed to correlate CBD plasma concentrations at a steady state to demographic, clinical, and pharmacological characteristics as well as seizure frequency after the administration of a purified CBD oil solution in a real-world setting of children with drug-resistant developmental and epileptic encephalopathies (DEEs). Patients receiving oral CBD pharmaceutical products at maintenance were enrolled. Venous blood samples were drawn before the CBD morning dose, 12 h apart from the last evening dose (C0 or CBD trough concentration). A linear mixed-effect analysis was implemented to assess the correlation between C0 and clinical, laboratory, pharmacological, and lifestyle factors. Fifteen females and seven males with a median age of 12.8 years (ranging between 4.7 and 17.2) were included. The median CBD dose was 8.8 mg/kg/day (ranging between 2.6 and 22.5), and the CBD C0 median (range) was 48.2 ng/mL (3.5-366.3). The multivariate model showed a 109.6% increase in CBD C0 in patients with concomitant levothyroxine (β = 0.74 ± 0.1649, p < 0.001), 56.8% with food (β = 0.45 ± 0.1550, p < 0.01), and 116.0% after intake of a ketogenic diet (β = 0.77 ± 0.3141, p < 0.05). All patients included were responders without evidence of an association between C0 and response status. In children with DEEs, systemic concentrations of CBD may be significantly increased when co-administered with levothyroxine, food, or a ketogenic diet.